2017
DOI: 10.1016/j.surfcoat.2017.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hardness and Young's modulus of electrodeposited Al–W alloy films by nano-indentation

Abstract: 14Al-W alloy films with various W contents up to ~12 at% were prepared by 15 electrodeposition using 1-ethyl-3-methylimidazolium chloride (EMIC)-AlCl3 ionic 16 liquids with different concentrations of W precursor, W6Cl12. The hardness (H) and 17 Young's modulus (E) of the films were examined by nano-indentation. The films were 18 composed of a single-phase fcc Al super-saturated solid solution, an amorphous phase, or 19 both, depending on the W content and the deposition conditions. The H value increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…44,45) We have previously examined AlW alloy films with up to ³12 at% W for hardness and Young's modulus, and showed that these alloy films are harder and have a higher ratio of hardness to Young's modulus than Al metal. 16) This study suggested that AlW alloy films with a higher W content could have an even higher mechanical strength.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…44,45) We have previously examined AlW alloy films with up to ³12 at% W for hardness and Young's modulus, and showed that these alloy films are harder and have a higher ratio of hardness to Young's modulus than Al metal. 16) This study suggested that AlW alloy films with a higher W content could have an even higher mechanical strength.…”
Section: Introductionmentioning
confidence: 78%
“…The prepared EMICAlCl 3 melt was stored in a 25-mL glass vessel used as an electrolytic cell. W 6 Cl 12 was synthesized by a method described in our previous report, 15,16) and was added to the melt maintained at 80°C throughout the experiment. The bath temperature was controlled by a thermostat (TJA-550, AS ONE) connected to a rubber heater wound around the cell and a thermocouple immersed in the bath.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanoindentation has become a mature technique for mechanical property identification and small lengthscale materials science research [1][2][3][4][5][6][7][8][9][10][11][12][13]. The load versus penetration depth curve (P-h curve) is used to determine the elastic modulus and hardness via the Oliver-Pharr method [4,5,14,15]. Indentation pop-in load is the force which the indentation transitions by a depth jump from the elastic to the elastoplastic regime.…”
Section: Introductionmentioning
confidence: 99%